Analisis Kualitas Ikan Bada Terbaik Menggunakan Metode Simple Additive Weighting - Novi Trisna; Annisak Izzaty Jamhur; Radius Prawiro (CESS (Journal of Computer Engineering, System and Science), 2021)
Mandeh area of the south coast of west Sumatra there are many business units selling bada fish. The business unit uses the invisible way of distinguishing good ikan bada for sale, in that way many customers complain because there are still many bada ikan that are not good mixed when purchased by customers. To solve it using a decision support system with a simple additive Weighting (SAW) method, this SAW method looks for Weighting summation of performance ratings of various alternatives that can be distinguished from several criteria. In determining good quality bada ikan then the criteria are distinguished into 5 criteria in terms of color, texture, taste, shape and smell.